2014
DOI: 10.1039/c4ce00544a
|View full text |Cite
|
Sign up to set email alerts
|

35Cl solid-state NMR of HCl salts of active pharmaceutical ingredients: structural prediction, spectral fingerprinting and polymorph recognition

Abstract: A series of HCl salts of active pharmaceutical ingredients (APIs) have been characterized via35Cl solid-state NMR (SSNMR) spectroscopy and first-principles plane-wave DFT calculations of 35Cl NMR interaction tensors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
101
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 57 publications
(110 citation statements)
references
References 93 publications
9
101
0
Order By: Relevance
“…It has been shown for chlorine anions in HCl API systems that have only one H-bonding contact shorter than 2.2 Å, that the magnitude of C Q generally increases as the contact distance shortens, and the sign of the calculated C Q is negative. 37 Indeed, the calculated value of C Q for the Diph Cl site is large and negative (C Q = −6.28 MHz), in agreement with these trends. Furthermore, the calculated value of η Q = 0.01 indicates a 35 Cl EFG tensor of near-axial symmetry with V 33 as the distinct component, also consistent with previous observations.…”
Section: Plane-wave Dft Calculations Of 35 CL Efg and Ns Tensorssupporting
confidence: 79%
See 1 more Smart Citation
“…It has been shown for chlorine anions in HCl API systems that have only one H-bonding contact shorter than 2.2 Å, that the magnitude of C Q generally increases as the contact distance shortens, and the sign of the calculated C Q is negative. 37 Indeed, the calculated value of C Q for the Diph Cl site is large and negative (C Q = −6.28 MHz), in agreement with these trends. Furthermore, the calculated value of η Q = 0.01 indicates a 35 Cl EFG tensor of near-axial symmetry with V 33 as the distinct component, also consistent with previous observations.…”
Section: Plane-wave Dft Calculations Of 35 CL Efg and Ns Tensorssupporting
confidence: 79%
“…[36][37][38][39] The application of 35 Cl SSNMR for the differentiation of polymorphs of HCl APIs in dosage forms is advantageous because most excipients do not contain chlorine; thus, any signals present in the 35 Cl SSNMR spectra are unique to the API.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been recently demonstrated that 35 Cl SSNMR can provide important structural information about the chlorine sites in different polymorphic forms in APIs, including the nature of the hydrogen bonding environments and impurity phases, in reduced experimental times compared to conventional pXRD and 13 C SSNMR experiments. 24,32,[39][40][41] For further reading on the use of SSNMR to characterize pharmaceutical compounds, we refer readers to recent reviews by Vogt and Monti et al [42][43][44] Given the ubiquity of nitrogen in functional groups such as amines, amides and numerous heterocycles, and the importance of intermolecular hydrogen-bonding interactions of nitrogen in solid APIs, the naturally occurring NMR-active nitrogen nuclei, 14 [55][56][57][58][59][60][61][62] and pharmaceuticals. 27,63-69 14 N nuclear quadrupole resonance (NQR) spectroscopy has also recently been applied, with some success, to a variety of APIs for purposes of quantification and polymorph differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…24 It has been shown, for 4 example, that chlorine EFG parameters can be correlated to the hydrogen-bonding environment. 25 Chlorine SS-NMR can be used as a structural probe for many materials. For example, it has been used as a technique for polymorph distinction and in the screening of hydrochloride (HCl)-containing APIs [25][26][27][28] as well as their dosage forms with excipients, which is difficult for other techniques.…”
Section: Introductionmentioning
confidence: 99%
“…25 Chlorine SS-NMR can be used as a structural probe for many materials. For example, it has been used as a technique for polymorph distinction and in the screening of hydrochloride (HCl)-containing APIs [25][26][27][28] as well as their dosage forms with excipients, which is difficult for other techniques. [29][30] Chlorine SS-NMR has also been used for the characterization of a chloride ion receptor, 21 alkaline earth chlorides (including hydrates) 24,31 and has been used to comment on halogen bonding [32][33][34] and ion dynamics in solids.…”
Section: Introductionmentioning
confidence: 99%